Sum of products

Let a , b , c , d N \displaystyle a,b,c,d \in \mathbb{N} where c a b d \displaystyle c\le a\le b\le d such that

{ a + b = c d c + d = a b \begin{cases} a+b=cd\\ c+d = ab \end{cases}

and let P = a b c d \displaystyle P=abcd .

Find the sum of all possible P P .


The answer is 46.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

X X
Jun 10, 2018

Notice that if x + y > x y x+y>xy ,then one of x x and y y must equal 1.

If a + b = a b , ( a 1 ) ( b 1 ) = 1 , a = b = 2 a+b=ab,(a-1)(b-1)=1,a=b=2 ,and also c + d = c d , c = d = 2 c+d=cd,c=d=2 .

If a + b < a b a+b<ab ,then c + d > c d c+d>cd ,and that means c = 1 c=1 .We get a + b = d , a b = d + 1 , a b a b = 1 , ( a 1 ) ( b 1 ) = 2 , a = 2 , b = 3 , d = 5 a+b=d,ab=d+1,ab-a-b=1,(a-1)(b-1)=2,a=2,b=3,d=5

If a + b > a b a+b>ab ,then a = 1 a=1 ,that means c = 1 c=1 .According to the above equation,if c = 1 c=1 then a = 2 a=2 ,so it doesn't fit.

Hence,P=16 or 30.

Chan Lye Lee
Oct 15, 2015

{ a + b = c d c + d = a b \displaystyle\begin{cases}a+b=cd \\ c+d=ab \end{cases} implies that { a + b c d = 1 c + d a b = 1 \displaystyle\begin{cases} \frac{a+b}{cd}=1\\ \frac{c+d}{ab}=1\end{cases} . This yields ( 1 a + 1 b ) ( 1 c + 1 d ) = 1 \displaystyle \left( \frac{1}{a}+\frac{1}{b}\right)\left( \frac{1}{c}+\frac{1}{d}\right)=1 .

Suppose 1 a + 1 b = 1 \displaystyle \frac{1}{a}+\frac{1}{b}=1 . Then a + b = a b \displaystyle a+b=ab which means that ( a 1 ) ( b 1 ) = 1 \displaystyle (a-1)(b-1)=1 . Since a , b N a,b \in \mathbb{N} , a 1 = b 1 = 1 a-1=b-1=1 , or equivalently, a = b = 2 a=b=2 . The assumption 1 a + 1 b = 1 \displaystyle \frac{1}{a}+\frac{1}{b}=1 also implies that 1 c + 1 d = 1 \displaystyle \frac{1}{c}+\frac{1}{d}=1 , which also means that c = d = 2 c=d=2 . Hence ( a , b , c , d ) = ( 2 , 2 , 2 , 2 ) \color{#3D99F6}{ (a,b,c,d)=(2,2,2,2)} is a solution.

If 1 a + 1 b > 1 \displaystyle \frac{1}{a}+\frac{1}{b}>1 , then a = 1 a=1 or b = 1 b=1 . However, this is impossible as c a b d c\le a\le b\le d implies that a = c = 1 a=c=1 which means ( 1 a + 1 b ) ( 1 c + 1 d ) = ( 1 + 1 b ) ( 1 + 1 d ) > 1 \displaystyle \left( \frac{1}{a}+\frac{1}{b}\right)\left( \frac{1}{c}+\frac{1}{d}\right)=\left( 1+\frac{1}{b}\right)\left( 1+\frac{1}{d}\right)>1 .

Therefore 1 a + 1 b < 1 \displaystyle \frac{1}{a}+\frac{1}{b}<1 . It is clearly seen that 1 c + 1 d > 1 \displaystyle \frac{1}{c}+\frac{1}{d}>1 which implies that c = 1 c=1 . From the equations { a + b = c d c + d = a b \displaystyle\begin{cases}a+b=cd \\ c+d=ab \end{cases} , we now have { a + b = d 1 + d = a b \displaystyle\begin{cases}a+b=d \\ 1+d=ab \end{cases} . By eliminating d d , we will obtain a + b = a b 1 a+b=ab-1 which means that ( a 1 ) ( b 1 ) = 2 (a-1)(b-1)=2 . Since a , b N a,b \in \mathbb{N} , a = 2 a=2 and b = 3 b=3 . Lastly, d = a + b = 5 d=a+b=5 . Hence ( a , b , c , d ) = ( 2 , 3 , 1 , 5 ) \color{#3D99F6}{ (a,b,c,d)=(2,3,1,5)} is another solution.

Finally, P = 2 4 + 2 ( 3 ) ( 1 ) ( 5 ) = 46 P=2^4+2(3)(1)(5)=\boxed{46} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...